Pre-, Per- and post-cooling strategies used by competitive tennis players in hot dry and hot humid conditions - Robin, Nicolas; Crespo, Miguel; Ishihara, Toru; Carien, Robbin; Brechbuhl, Cyril; Hue, Olivier; Dominique, Laurent (Frontiers in Sports and Active Living, 2024)
This research investigated the pre-, per- and post cooling strategies used by competitive tennis players from various levels of play who occasionally train and compete in hot (> 28°C) and humid (> 60% rH), and dry (< 60% rH) environments. 129 male tennis players (M age = 24.9) competing at regional (N=54), national (N=30) and international (N=45) levels, completed an online questionnaire regarding their use of pre-, per- and postcooling strategies when playing tennis in hot dry (HD) and hot humid (HH) conditions. Competitive tennis players used both internal and external cooling strategies to combat the negative effects of HD and HH conditions, but considered the HH to be more stressful than HD and experienced more heat-related illness in HH environments. International players used cold packs and cold towel more frequently than the regional and national players in hot environments, and used cold water immersion and cold vest more frequently than the latter in HH. Differences in strategy use were mostly observed during per-cooling where regional and national players more frequently used cold drinks than international players who more frequently used cold packs in HD and cold towel in HH conditions. Moreover the latter more frequently used cold towel, cold packs and cold water immersion as post-cooling strategies than regional players. In the heat, it is recommended to employ cooling strategies to maintain health, limit declines in performance, and promote recovery. We recommend improving education regarding the appropriate use and effectiveness of cooling strategies, and increasing their availability in tournaments.